Експериментально-клінічне дослідження можливості автотрансплантації тканин щитоподібної та прищитоподібних залоз для корекції гормональної недостатності - Афонін, Д. М. (Clinical Endocrinology and Endocrine Surgery, 2010)
As a study material we used 117 adult male non-linear rats and the results of clinical observation of 57 patients with two-sided multinodular euthyroid goiter. A complex study of the morphological properties of the grafted thyroid and parathyroid tissues, serum calcium, and also biochemical tests after performed grafting proved functional sufficiency of the complex autografts. Efficacy of postoperative autografting for clinic was also proved by immune tests of serum thyroid and parathyroid hormones levels, thyroid status tracking, blood calcium level measurements and also by radio isotopic assays and immune reactions for grafting. In this study we demonstrated that intraoperative heterotopic autotransplantation of thyroid and parathyroid tissues allow compensation of hypothyroidism and hypoparathyroidism manifestations that develop after thyreoectomy. The analogous results were obtained after clinical application of the method. Here we also noted functional sufficiency of a new endogenic thyroid and parathyroid source that allows avoiding HRT. Immunity showings after operation were also noted as having positive changes. The study gives the evidence that the proposed method is effective and allows to reduce the frequency and severity of hypothyroidism and hypoparathyroidism in the late postoperative period.